Discovery of STAT3 Inhibitors: Recent Advances and Future Perspectives - Song, Jiatao; Wang, Jiawei; Tian, Sheng; Li, Huanqiu (Current Medicinal Chemistry, 2023)
Background: STAT3 (signal transducer and activator of transcription 3) is a member of the STAT family of proteins that function as signal transducers and transcription factors. Previous research has demonstrated its importance in cell proliferation, differentiation, apoptosis, and immunological and inflammatory responses. Targeting the STAT3 protein has recently been hailed as a viable cancer therapeutic method. Even though none of these inhibitors have yet been exploited in clinical cancer therapy, a small number have made them into clinical trials, leading researchers to explore more promising inhibitors. Methods: Based on the mechanism of STAT3 activation, several types of STAT3 inhibitors were described and summarized according to their origins, structures, bioactivity and mechanism of action. Direct inhibition of STAT3 mainly targeted one of the three distinct structural regions of the protein, namely the SH2 domain, the DNA binding domain, and the coiled-coil domain. Results: The progress in STAT3 inhibitor discovery from 2010 to 2021 is comprehensively summarized in this review. STAT3 inhibitors are mainly classified into small molecule inhibitors, natural product inhibitors, and peptides/peptidomimetics. Moreover, it also covers relevant analogues, as well as their core framework. Conclusion: Small-molecule inhibitors of STAT3 like BP-1-102 and BTP analogues displayed great potential against various cancers, while natural products, as well as peptide and peptidomimetics, also showed promising application. Therefore, STAT3 has become a promising target with great research value, and the development of STAT3 inhibitors may provide more therapeutic strategies for STAT3-related diseases.
Keywords: cell proliferation